REPRESENTASI MOTHERHOOD PADA KARAKTER HANTU PEREMPUAN DALAM FILM PENGABDI SETAN - Dany Dwi Saputra; Hapsari Dwiningtyas Sulistyani (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
Motherhood has become one of many main narratives that frequently appeared in horror films. Mother has been mainly used as a character who terrorizes and haunts children, specifically. This sort of representation possibly enable stereotypes and giving certain images to mothers in Indonesia, whom majority of people look upon as noble. Film as the portrait of society has been used to establish submission among people towards agendas and interests of authorities. This research aims to examine the representation of motherhood on female ghost character in Pengabdi Setan. Feminist film theory and semiotic communication theory are used for this research. This research will apply Sara Mills’ critical discourse analysis to look deeper on four aspects of examinations consist of character, fragmentation, focalization and schemata. The results indicate that female ghosts characters exhibit the aspects of motherhood. Through their physical (bodily) aspects, characters of Mawarti (1980) and Mawarni (2017) as ghosts, are portrayed as physically non-sexual and desireless. Whereas their maternal roles tend to have corrupt qualities, for trying to egoistically dominate their children’s lives. Fragmentation of maternal bodies of the characters, denote the grotesque and menacing femininity through the depictions of face/head, hands and back. Maternal bodies are portrayed as source of horrors for their children. Focalization in both movies indicate that both ghosts are passive objects. Maternal subjectivities from both ghosts, who also happen to be mothers, are altogether not presented, and rendered through male-oriented point of view (focalization). Schemata finally points that, a mother naturally has superior social role, with the expense of rigid order by dominant ideology. In that case, female roles as mothers are controlled. Female power are viewed as archaic for its nature aligned with transgression. At last, a mother will never wholly empowered, without fulfillment of her prescribed expectations.